2015
DOI: 10.1016/j.ijscr.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Gastrobronchial fistula following minimally invasive esophagectomy for esophageal cancer in a patient with myotonic dystrophy: Case report

Abstract: HighlightsMyotonic dystropy patients have after major surgery increased risk for pulmonary complications because of weakness of respiratory muscles.Such a patient tolerated a minimally invasive esophagectomy for cancer.Minimally invasive instead of open surgery was probably the only feasible treatment due to less strain on respiratory function.A life-threatening complication of gastrobronchial fistula healed by stenting of the gastric conduit and ventilation with low airway pressures.Indications for stenting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Conservative treatment is also a possible option. Hugin et al 15 reported on the successful cure of a gastrobronchial fistula between the right intermediary bronchus and the esophagogastric anastomosis using ventilation maintained at low airway pressures, combined with a partially covered wall flex stent placed in the esophageal and gastric remnant. Non-surgical treatment could effectively occlude the fistula and act as a bridge treatment, and the application of a tracheal stent could improve the patient's general condition before the trachea is suitable for surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is also a possible option. Hugin et al 15 reported on the successful cure of a gastrobronchial fistula between the right intermediary bronchus and the esophagogastric anastomosis using ventilation maintained at low airway pressures, combined with a partially covered wall flex stent placed in the esophageal and gastric remnant. Non-surgical treatment could effectively occlude the fistula and act as a bridge treatment, and the application of a tracheal stent could improve the patient's general condition before the trachea is suitable for surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients with type II AGF were healed. Some authors claim that the patients with AGF can benefit from early stent placement (10)(11)(12)25). However, based on the results from a Mantel-Haenszel analysis, Boyd concluded that though airway stenting for AGF was associated with an initial closure rate of 75%, there was a high recurrence rate of 39%.…”
Section: Discussionmentioning
confidence: 99%
“…The literature are comprised mainly case reports, and, as a consequence, there is no ideal therapeutic principle that can be recommend. General conservative treatments include jejunostomy feeding, fasting, the administration of proton pump inhibitors and NGT drainage (7), bronchoscopy (8)(9)(10)(11) or gastroscopy (12) and stent insertion. These treatments have shown to achieve reliable good results in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Management is patient-tailored and depends on several factors such as the clinical status, blood supply of the gastric conduit and fistula characteristics (cause, dimensions, site) 2 11. The vast majority of cases require a one- or two-stage surgical intervention 11 21. The most widespread approach is a one-stage procedure and consists of direct fistula dissection and closure of the underlying gastric and bronchial defect, with or without vital tissue interposition 11.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific circumstances of GBFs, conservative management is seldom feasible 19. To date, only five cases with conservative management, although with variable success, have been reported 2 12 17 18 21 22…”
Section: Discussionmentioning
confidence: 99%